Design of an Encrypted Serial Communication System Based on Pseudo-random Sequences - LI Miao; FAN Linbin; WANG Yan (Kongzhi Yu Xinxi Jishu)
In some low-cost industrial application scenarios, serial communication is mostly transmitted in plaintext, leaving data vulnerable to theft and issues, such as poor data reliability. To enhance data security during transmission and communication reliability, this paper proposes an encrypted serial communication system based on pseudo-random sequences. The system adopts the technologies of arbitrary series pseudo-random sequence generation, dynamic sampling window adjustment, and serial code stream scrambling to realize non-transparent data transmission via channels. At the receiving end, pseudo-random sequences are synchronized through capturing the header, allowing for serial code stream decoding and data information acquisition. Within an environment of the communication system created by using field-programmable gate array (FPGA), experiments revealed the maximum baud rate at 20 Mbit/s, which could meet the encryption requirements of m-sequences of 4~15 series, and yielded good results.